Dasar Pertimbangan Hakim Dalam Putusan Perkara Hak Asuh Anak Di Pengadilan Agama Gorontalo - Ricca Aditya; Fence M Wantu; Julisa Aprilia Kaluku (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to find out and analyze the methods used by judges in deciding child custody cases and what considerations judges use in deciding child custody in the Gorontalo religious courts. The research method used in this research is a normative juridical type of research, and the research approach used in the research uses a qualitative type of approach. Apart from that, the author also uses a statutory approach related to the methods and considerations of judges who are the focus of this research. The location of this research is the Gorontalo City Religious Court. The research results obtained by researchers are that the methods used in deciding on custody are varied, including interpretation, argumentation, exposition and the main consideration in terminating child custody is the interests or prioritization of the child itself, starting from material and mental aspects. This proves that rechvinding or the judge's discovery is important if no new rules are found, this will certainly help in terminating custody disputes where the decision is still unclear.